Leadership in healthcare - Hrbáčová, Eliška (2019)
The aim of thesis is to evaluate and compare various physician leadership competencies in the Czech healthcare environment. Theoretical part of the thesis reviews the literature regarding the topic of leadership. The methodology used in this thesis is a survey based upon a questionnaire by Gallagher Integrated Healthcare Strategies. The procedure was to distribute the survey among the highest number of medical personals across the healthcare system in the Czech Republic. Conclusion of the thesis consists of recommendations for leadership competency development.